Corporate governance in the aftermath of the global financial crisis. - Rezaee, Zabihollah, 1953- (Financial accounting and auditing collection., 2018)
This timely and relevant book describes the practice of good governance in the aftermath of recent global crisis with a keen focus on internal and external corporate governance mechanisms to address future global challenges. Corporate governance measures are accelerating, converging, and reshaping organization structure, corporate culture, ethics and trust, transparency, roles, responsibilities, and accountability of all corporate functions. This book presents a road map for various functions and measures of corporate governance in addressing global financial, capital market and economic challenges. Written in a practical and succinct style, it will focus on internal corporate governance mechanisms and incorporate provisions of the Sarbanes-Oxley Act of 2002, Dodd-Frank Act of 2010, JOBS Act of 2012, the Securities and Exchange Commission (SEC)-related implementation rules, and global corporate governance best practices into all chapters throughout the book. This book presents the essential and fundamental concepts of corporate governance with a keen focus on a new holistic approach that addresses all corporate activities, performance, reporting, and assurance.